Carbetocin in the prevention of postpartum hemorrhage - Din, Mehraj; Irtika,; Adfar, Aneeka; Ashraf, Hanzilla; Siddiqui, Iram; Zaman, Bashir U. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Postpartum hemorrhage (PPH) is the most common and a potentially life-threatening complication of childbirth in both vaginal and caesarean deliveries. Carbetocin is a newer analogue of oxytocin with longer half-life and more heat stable. This study was aimed to assess the efficacy of carbetocin in the prevention of postpartum hemorrhage (PPH) in vaginal and caesarean deliveries, at a single tertiary care centre. Methods: A total of 130 pregnant patients included in the study received a bolus of carbetocin 100 µg i.v./i.m. at the delivery of anterior shoulder. After patients received uterotonic agent (carbetocin), patients were observed for 24 hours. The change in hemodynamic and clinical variables such as drop in hematocrit than one obtained on admission was observed. Clinical signs such as pallor, cold clammy skin, hypotension and tachycardia were also noted. In addition uterine tone after receiving carbetocin was also noted. Results: There were comparable hemodynamic parameters in terms of heart rate, SBP and DBP in the pre-labor and post-labor. Most of the patients 54.6% (n=71) had contracted uterine tone followed by well-contracted in 35.4% (n=46). There was no significant difference found in terms of hemoglobin concentration and hematocrit in pre-labor and post-labor. 3.1% (n=4) patients experienced PPH. 6.15% (n=8) needed blood transfusion. No adverse effects or complications or maternal mortality was observed in the present study. Conclusions: This study concludes that using carbetocin in the third stage of labour resulted in decreased incidence of post-partum hemorrhage, decreased blood transfusion as well as decreased use of additional uterotonics.